Implementasi E-Commece dan Membangun Branding dalam Peningkatan Penjualan Kopi pada Usaha Mikro, Kecil dan Menengah Desa Mayang - Rakhmayudhi, Rakhmayudhi; Purwanti, Santi; Subagja, Yuda Candra; Setiawan, Dika (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Coffee is a drink that has many fans, so almost every stall, shop, café, even restaurant always provides drinks with a distinctive taste and aroma that can increase enthusiasm in carrying out daily routines. Mayang Village has several MSMEs, one of which is MSMEs engaged in the processing of Mayang coffee drinks. In the business process, it is desirable for an increase in promotion and wider sales. Seeing the potential that exists, to increase sales of Mayang coffee drinks, it is necessary to make branding both from the logo and packaging of Mayang coffee bottles. In addition, to increase sales, it is necessary to implement e-commerce using the shopee platform so that promotions can be wider and provide easy transactions and interactions for sellers and buyers